Microbiome and lipidomic analysis reveal the interplay between skin bacteria and lipids in a cohort study - Li, Min; Kopylova, Evguenia; Mao, Junhong; Namkoong, Jin; Sanders, Jon; Wu, Joanna (Frontiers in Microbiology, 2024)
Human skin acts as a protective barrier between the body and the external environment. Skin microbiome and intercellular lipids in the stratum corneum (SC) are essential for maintaining skin barrier function. However, the interplay between skin bacteria and the lipids is not fully understood. In this study, we characterized the skin microbiome and SC lipid profiles from the forearm and face in a cohort of 57 healthy participants. 16S rRNA gene sequencing showed the skin microbial composition is significantly different between body locations and genders. Female forearm samples have the highest microbial diversity. The relative abundance of Staphlycoccous hominis, Micrococcus luteus, Corynebacterium tuberculostearicum, Finegoldia magna and Moraxellaceae sp. are significantly higher in the forearm than the face. The predictive functional analysis of 16S rRNA gene sequencing by Phylogenetic Investigation of Communities by Reconstruction of Unobserved States (PICRUSt2) and ANCOM-BC showed different bacterial metabolic pathway profiles between body locations or genders, and identified 271 differential pathways, including arginine and polyamine biosynthesis, chorismate biosynthesis pathways, which are more abundant in the female forearm, and sulfur oxidation pathway, which is more abundant in the male face. The SC lipid profiles differ between the body locations as well. Total free fatty acids (FFA), cholesterol sulfate and sphingosine are more abundant in the face. Dihydro-/6-hydroxy/phyto-ceramides are more abundant in the forearm. The correlation analysis of 16S rRNA gene sequencing and lipids revealed novel interplay between the bacteria and skin lipids. Shannon entropy and S. hominis negatively correlated with FFA, cholesterol sulfate and sphingosine; while positively correlated with dihydro-/6-hydroxy/phyto-ceramides. The correlation of predictive pathway profiles and lipids identified pathways involved in amino acids metabolism, carbohydrates degradation, aromatic compounds metabolism and fatty acid degradation metabolism are positively correlated with dihydro-/6-hydroxy/phyto-ceramides and negatively correlated with FFA, cholesterol sulfate and sphingosine. This study provides insights on the potential correlation between skin microbiome and lipids